The tumor suppressor 5A2, a synthetic miR-7-5p mimic, targets oncogenic and metabolic pathways, as revealed by transcriptome-wide analysis - Marion T. J. van den Bosch; Bryony J. Telford; Sanaz Yahyanejad; Thijs de Gunst; Harm C. den Boer; Rogier M. Vos; Chantal L. Duurland; Rianne Biemans; Ludwig J. Dubois; Laurens A. H. van Pinxteren; Roel Q. J. Schaapveld; Michel Janicot (Frontiers Media S.A., 2023)
As cancer is a multifactorial disease, the multimodal action of microRNAs makes them an attractive tool for novel therapeutic approaches. The tumor suppressive miR-7-5p has been shown to act on many aspects of oncogenesis, including cell proliferation, migration and angiogenesis, by targeting a spectrum of key genes. We developed a synthetic chemically modified miR-7-5p mimic, 5A2, and performed a comprehensive functional characterization in a panel of human cancer cell lines. 5A2 reduced cell proliferation in most cell lines by inducing cell cycle arrest. To enable systemic delivery of 5A2 to tumors, it was formulated in a novel lipid nanoparticle (INT-5A2) and we demonstrated the anti-tumor activity of INT-5A2 in an experimental human liver tumor-bearing mouse model. Next, RNA-sequencing was used to gain more insight into the molecular mechanism of action of 5A2 and demonstrated a broad repression of target mRNAs. Interestingly, Ingenuity Pathway Analysis revealed a new role for 5A2 in metabolic pathways. Validation experiments in vitro showed that 5A2 reduced the expression of key glycolysis and glutaminolysis enzymes, leading to a decrease in glycolysis, lactate secretion and intracellular glutamate availability. Taken together, these data strongly suggest that miR-7-5p/5A2 is a potent tumor suppressor that targets various key cellular pathways across cancer types. Therefore, 5A2 may represent a promising novel treatment strategy in oncology.